Diagnostic accuracy of ultrasound & X-Ray KUB in Ureteric Colic taking CT as gold standard - Syed Muhammad Faiq; Nazish Naz; Zaidi, Fatima Batool; Rizvi, Adeeb ul Hassan (International Journal of Endorsing Health Science Research, 2014)
The objective of the study was to compare the sensitivity and specificity of ultrasound, X-ray KUB and CT for the diagnosis of ureteral colic in patients with acute flank pain. This study was carried out in Department of Radiology Sindh Institute of Urology and Transplantation (SIUT) from Aug 2010 to Nov 2010. A total of 190 patients with mean age of 35 years were included in the study. All individuals underwent pre procedural imaging X-ray KUB, U/S and CT. On these imaging modalities obstruction of urinary tract and stones were determined. X-ray KUB was done as a guide for U/S exam only. Ureteral stones were confirmed in 190 patients. Specificity for ct was 100% whereas X-ray KUB and U/S was 94% and 76% respectively. Sensitivity for CT 100%, U/S 52.6% and X-ray KUB 89.5% respectively. Some stones were not detected by U/S and few stones were not detected on X-ray KUB due to bowel gases. Cases were correctly diagnosed with all three techniques. CT is the most reliable technique for the detection of uretric stones however, X-ray and U/S also be chosen alternative to CT with a reduce radiation dose.